2021
DOI: 10.1002/adfm.202104864
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Single Copper Atoms to Microporous Carbon Spheres as High‐Performance Electrocatalyst for Oxygen Reduction Reaction

Abstract: Although the carbon-supported single-atom (SA) electrocatalysts (SAECs) have emerged as a new form of highly efficient oxygen reduction reaction (ORR) electrocatalysts, the preferable sites of carbon support for anchoring SAs are somewhat elusive. Here, a KOH activation approach is reported to create abundant defects/vacancies on the porous graphitic carbon nanosphere (CNS) with selective adsorption capability toward transition-metal (TM) ions and innovatively utilize the created defects/ vacancies to controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 65 publications
2
82
0
Order By: Relevance
“…No peaks associated with crystalline Fe were observed for the samples (Figure S11, Supporting Information), and only one broad peak in the range of 20-30 degree, correspond to the (002) plane of graphite carbon. [45][46][47] This result further supports the conclusions of TEM and HAADF-STEM that the Fe in the Fe-PpPD-800 exists as single atom. Notably, XRD analysis of Fe-PpPD-T at different treatment temperatures showed that the characteristic peaks of iron-based species appeared when the temperature increased to 900 °C or higher (Figure S12, Supporting Information), indicating the Fe aggregates into crystalline species rather than atomically dispersed species under high temperature conditions.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…No peaks associated with crystalline Fe were observed for the samples (Figure S11, Supporting Information), and only one broad peak in the range of 20-30 degree, correspond to the (002) plane of graphite carbon. [45][46][47] This result further supports the conclusions of TEM and HAADF-STEM that the Fe in the Fe-PpPD-800 exists as single atom. Notably, XRD analysis of Fe-PpPD-T at different treatment temperatures showed that the characteristic peaks of iron-based species appeared when the temperature increased to 900 °C or higher (Figure S12, Supporting Information), indicating the Fe aggregates into crystalline species rather than atomically dispersed species under high temperature conditions.…”
Section: Resultssupporting
confidence: 85%
“…Moreover, no diffraction spots were detected in the corresponding selected area electron diffraction (SAED) pattern, further confirming the no iron-based nanoparticles were formed in FePpPD-800 (see inset in Figure 1c). Furthermore, the high-resolution TEM image (Figure 1d) only observed a 0.34 nm lattice spacing fringe, attributed to the (002) plane reflection of the graphitic carbon, [44,45] again confirming the absence of iron particles. Similarly, no iron-based nanoparticles were observed for the samples Fe-PoPD-800 and Fe-PmPD-800 (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 81%
“…Among them, Cu-SAs@N-CNS exhibits the best ORR performance, with an E 1/2 of 0.90 V ( vs. RHE) and a limiting diffusion current density of −5.50 mA cm −2 in 0.1 M KOH solution. 136 The as-prepared nanofibers are treated with N 2 plasma to increase the number of defects and the N doping amount in the carbon substrate (Fig. 10b).…”
Section: General Strategies For Stabilizing Metal Atomsmentioning
confidence: 99%
“…Generally, increasing the number of active sites and optimizing the electronic structure of active site are two effective strategies to boost the catalytic activity of electrocatalysts. However, increasing the number of active sites of SACs by increasing the metal atomic load remains a challenge since metal atoms tend to agglomerate into nanoparticles during pyrolysis, which is detrimental to their electrocatalytic performance . Based on SACs that are formed by dispersed metal atoms immobilized on the substrate, the size and morphology of the substrate material will significantly affect the exposure of the catalytically active sites of SACs. , Substrate materials with relatively thick dimensions result in a large number of metal active sites being buried inside of the carbon matrix, which cannot be fully utilized. For this reason, under a fixed metal atom load, achieving sufficient exposure of metal active centers will further improve the intrinsic catalytic activity of SACs.…”
mentioning
confidence: 99%
“…23 Based on SACs that are formed by dispersed metal atoms immobilized on the substrate, the size and morphology of the substrate material will significantly affect the exposure of the catalytically active sites of SACs. 24,25 Substrate materials with relatively thick dimensions result in a large number of metal active sites being buried inside of the carbon matrix, which cannot be fully utilized. For this reason, under a fixed metal atom load, achieving sufficient exposure of metal active centers will further improve the intrinsic catalytic activity of SACs.…”
mentioning
confidence: 99%